Facile self-assembly-based fabrication of a polyvinylidene fluoride nanofiber membrane with immobilized titanium dioxide nanoparticles for dye wastewater treatment. (10th December 2022) - Park, Mijeong; Ko, Yun Taek; Ji, Myeongjun; Cho, Jae Sang; Wang, Dong Hwan; Lee, Young-In
Abstract: Photocatalytic membrane technology has received significant research attention because this system can continuously and safely purify wastewater without the post-process of separating and recovering the nanoscale photocatalysts. However, conventional membrane technology cannot wholly derive the photocatalytic performance due to the limitation in the loading contents of nanoscale photocatalyst and the reduced reactive sites. In this study, in order to overcome these issues and the limitations of current fabrication methods for photocatalytic membranes, a versatile and facile self-assembly approach for a polyvinylidene fluoride (PVDF) fiber-based reusable photocatalytic membrane with immobilized titanium dioxide (TiO2 ) nanoparticles is demonstrated to maximize the loading contents and photocatalytic reaction sites of nanoparticles on the surface of polymeric membrane. The TiO2 nanoparticles were successfully immobilized in high loading content on the surface of electrospun PVDF fibers using a poly(styrene-alt-maleic anhydride) as a self-assembly reaction agent at room temperature. Then, the physicochemical properties of the fabricated photocatalytic membrane and the manufacturing mechanism are systematically characterized. The photocatalytic properties of the membrane according to the loading of immobilized TiO2 nanoparticles are evaluated based on the degradation of various dye solutions under the illumination of a Xenon lamp (incident light intensity = 100 mW/cm 2 ). The photocatalytic performance of the membrane is considerably enhanced when the loading of immobilized TiO2 nanoparticles on the PVDF fibers is higher as a result of a more vigorous self-assembly reaction. Furthermore, the reusability of the membrane is evaluated by repeating the dye removal process via adsorption and light irradiation; after the 20th cycle, it is demonstrated that the dye removal efficiency remains high without any leakage of TiO2 nanoparticles. The proposed facile fabrication method for a photocatalytic membrane with excellent reusability thus offers a new approach for the design of industrially applicable high-efficiency photocatalytic membranes. Graphical abstract: Image 1 Highlights: Open up a facile way to fabricate photocatalytic membranes with high performance. TiO2 nanoparticles were spontaneously immobilized on PVDF fiber by self-assembly. A self-assembly agent was suggested to immobilize the nano-scale photocatalyst. This process maximizes the surface loading contents and photocatalytic reaction sites. The developed membrane showed outstanding performance, stability, and reusability.